Pengaruh Profitabilitas dan Struktur Modal Terhadap Nilai Perusahaan dengan Skor ESG Katadata Sebagai Variabel Moderasi: Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Periode 2023–2024 - Elinal Magfiroh; Mekani Vestari (Universitas Methodist Indonesia, 2026)
This study investigates the effect of profitability and capital structure on firm value, with Environmental, Social, and Governance (ESG) serving as a moderating variable in non-financial companies listed on the Indonesia Stock Exchange during the 2023–2024 period. Profitability is measured using Earnings per Share (EPS), capital structure is proxied by the Debt to Equity Ratio (DER), and firm value is measured by Price to Book Value (PBV), while ESG performance is assessed using the ESG Green Katadata score. This research employs secondary data obtained through purposive sampling, resulting in 294 observations that form an unbalanced panel dataset. Panel data regression with a Moderated Regression Analysis (MRA. The findings indicate that EPS does not have a significant effect on firm value, whereas DER and ESG have a negative and significant effect on firm value. ESG does not moderate the relationship between profitability and firm value but strengthens the effect of capital structure on firm value. In addition, firm size has a positive effect, while asset growth has a negative effect on firm value. These results suggest that firm value in the non-financial sector is more strongly influenced by financing decisions and sustainability factors than by short-term earnings performance.